Property crime and macroeconomic variables in Malaysia: Some empirical evidence from a vector error-correction model - Habibullah, M.S.
In this study we investigated the long-run relationship between property crime and three macro-financial economic variables in Malaysia for the period 1973 to 2003. In order to avoid what the econometrician term as ‘spurious regression problem’ we estimate the model using the vector-error correction (VECM) framework. The results tend to suggest that there are long-run relationship between property crime and the three macroeconomic variables in Malaysia. Our VECM results, however, suggest that there is no long-run and short-run causal effect of the three macro-variables on the property crime. Nevertheless, our variance decomposition results indicate that property crime in Malaysia is affect by economic growth measure by real income per capita. But, given the short sample nature of this study, our results should be viewed with cautious.property crime; Malaysia; vectot error-correction model